American Palestine : Melville, Twain, and the Holy Land mania - Obenzinger, Hilton (Princeton University Press, 1999)
In the 19th century, American tourists, scholars, evangelists, writers and artists flocked to Palestine. Focusing on works by Melville and Twain, this book throws new light on the construction ot American identity in the 19th century.